Short‐term complications of intra‐operative radiotherapy for early breast cancer. Issue 4 (11th January 2016) - Zur, Maoz; Shai, Ayelet; Leviov, Michelle; Bitterman, Arie; Shiloni, Eitan; Ben Yosef, Rahamim; Steiner, Mariana
Abstract : Introduction: IORT is becoming an accepted radiotherapy technique for treatment of early breast cancer. Data regarding the early complications of breast IORT are lacking. Objectives: Assess the nature and risk factors for early complications of breast conserving surgery (BCS) and intraoperative radiotherapy (IORT) with INTRABEAM®. Methods: IORT with INTRABEAM® was administered to breast cancer patients in Carmel Medical Center as part of an institutional clinical registry project. Three hundred and ninety five patients treated during 2006–2013 were included. Clinical and treatment data and data regarding complications documented within 1 year of surgery were collected. The association between clinical and treatment variables and risk of complications was assessed. Results: Complications were documented in 108 (27.3%) of patients. Grade III or IV complications were found in 5% of patients. Infections were diagnosed in 43 (10.8%) patients, seroma in 40 (10.1%), wound dehiscence in 32 (8.1%), and bleeding and hematomas in 11(2.8%). Two patients had a small size skin necrosis. Sixteen patients with a seroma had a secondary complication. All complications resolved. Diabetes mellitus and use of anticoagulants were associated with an increased risk of wound dehiscence and bleeding, respectively. Conclusions: IORT for breast cancer is safe in appropriately selected patients. Careful surgical technique and postoperative care is prudent. J. Surg. Oncol. 2016;113:370–373 . © 2016 Wiley Periodicals, Inc.